Collectin-11 (CL-11) Is a Major Sentinel at Epithelial Surfaces and Key Pattern Recognition Molecule in Complement-Mediated Ischaemic Injury - Nauser, Christopher L.; Howard, Mark C.; Fanelli, Giorgia; Farrar, Conrad A.; Sacks, Steven (Frontiers in Immunology, 2018)
The complement system is a dynamic subset of the innate immune system, playing roles in host defence, clearance of immune complexes and cell debris, and priming the adaptive immune response. Over the last 40 years our understanding of the complement system has evolved from identifying its presence and recognizing its role in the blood to now focusing on understanding the role of local complement synthesis in health and disease. In particular, the local synthesis of complement was found to have an involvement in mediating ischaemic injury, including following transplantation. Recent work on elucidating the triggers of local complement synthesis and activation in renal tissue have led to the finding that Collectin-11 (CL-11) engages with L-fucose at the site of ischaemic stress, namely at the surface of the proximal tubular epithelial cells. What remains unknown is the precise structure of the damage-associated ligand that participates in CL-11 binding and subsequent complement activation. In this article, we will discuss our hypothesis regarding the role of CL-11 as an integral tissue-based pattern recognition molecule which we postulate has a significant contributory role in complement-mediated ischaemic injury.